2013
DOI: 10.1002/ange.201301397
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Paclitaxel‐Conjugated β‐Cyclodextrin Polyrotaxane and Its Antitumor Activity

Abstract: Zellgängig: Ein β‐Cyclodextrin‐Polyrotaxan mit Poly(propylenglycol) als Achse und β‐Cyclodextrin als Endgruppe wurde synthetisiert. Konjugation des Tumortherapeutikums Paclitaxel an dieses Polyrotaxan ergab ein Konstrukt, das tief in Tumoren eindringt, deren Wachstum hemmt und das Leben tumortragender Mäuse besser als Taxol verlängert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Beyond their characterization as MRI contrast agents, only two studies using tumor bearing mice and single PR architectures have been reported with biodistributions occurring predominantly in the liver. 31 , 32 Additional studies showing PR biocompatibility with blood components (e.g., platelets, fibrinogen, and albumin) in vitro, anticoagulant activity (e.g., inhibition of platelet cytoplasmic calcium increase and an increased clot formation time), and reduced fibrinogen binding to polyurethane surfaces with PR modification 33 35 have been reported; however, no data are available with regard to the PK, BD, and toxicity of PR materials as a function of their molecular and supramolecular structure. Understanding this relationship is crucially important because PRs can be synthesized with a vast diversity of polymer precursors and macrocycle types, and molar ratios can produce variations in PR average molecular weights, macrocycle copy numbers, and threading efficiencies that may dramatically affect their biological performance.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their characterization as MRI contrast agents, only two studies using tumor bearing mice and single PR architectures have been reported with biodistributions occurring predominantly in the liver. 31 , 32 Additional studies showing PR biocompatibility with blood components (e.g., platelets, fibrinogen, and albumin) in vitro, anticoagulant activity (e.g., inhibition of platelet cytoplasmic calcium increase and an increased clot formation time), and reduced fibrinogen binding to polyurethane surfaces with PR modification 33 35 have been reported; however, no data are available with regard to the PK, BD, and toxicity of PR materials as a function of their molecular and supramolecular structure. Understanding this relationship is crucially important because PRs can be synthesized with a vast diversity of polymer precursors and macrocycle types, and molar ratios can produce variations in PR average molecular weights, macrocycle copy numbers, and threading efficiencies that may dramatically affect their biological performance.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with other reports which have demonstrated that PR behaves as random coils in good solvents, which explains their small sizes and spherical appearances. 20 …”
Section: Resultsmentioning
confidence: 99%
“…For example, Yu et al used PEG oligomer as the side chain of polyrotaxanes (PR) and then linked PTX with a high drug loading content of ∼29 wt %. 16 The PR-PTX conjugate exhibited a unique in vivo fate, significant antitumor response, and deep intratumoral penetration.…”
Section: Introductionmentioning
confidence: 99%